Learning in Social Networks: Rationale and Ideas for Its Implementation in Higher Education - Marialexa Olivera-Smith; Ibis M. Alvarez (MDPI AG, 2013)
The internet has fast become a prevalent medium for collaboration between people and social networks, in particular, have gained vast popularity and relevance over the past few years. Within this framework, our paper will analyse the role played by social networks in current teaching practices. Specifically, we focus on the principles guiding the design of study activities which use social networks and we relate concrete experiences that show how they contribute to improving teaching and learning within a university environment.